Analisis Sistem Insentif dalam Meningkatkan Kinerja Karyawan pada PT. Lasozihono GH Wings Air Bandar Udara Binaka (Jurnal Riset Manajemen dan Akuntansi, 2025)
The incentive system is one of the important factors that influence employee performance. Incentives that are well-designed and properly implemented can enhance employee motivation, productivity, and loyalty to the company. This study aims to analyze the implementation of the incentive system at PT. Lasozihono GH Wings Air and its impact on employee performance. Based on initial observations, issues were found such as salary dependency on flight target achievement and unfair bonus distribution. These problems create pressure, financial uncertainty, and potential conflicts among employees, which negatively affect performance. The findings of this study are expected to provide recommendations for developing a fair, transparent, and effective incentive system to support improved performance and the achievement of company goals. The purpose of this research is to understand the incentive system in enhancing employee performance at PT. Lasozihono GH Wings Air Binaka Airport, to identify the challenges faced in improving employee performance, and to explore solutions related to incentive distribution to support performance improvement. This study uses a qualitative research approach. Data collection techniques used in this study include observation, interviews, and documentation. The study aims to evaluate the incentive system and its impact on employee performance at PT. Lasozihono GH Wings Air. The results show that the incentive system has been implemented based on performance evaluation, but it is not yet fully transparent and equitable. Several issues were identified, including unclear rewards based on years of service, lack of attention to employee needs, and unfair distribution of incentives. Despite these challenges, employees demonstrate high performance in terms of discipline, productivity, punctuality, effectiveness, and independence. The incentives provided have contributed to increased work motivation. These findings indicate the need for improvements to the incentive system to make it fairer, more transparent, and more responsive to employee conditions.